An optimization problem of packing identical circles into a multiply connected region. Part 2. A solution method and its realisation - Stoyan, Yu.G.; Chugay, A.M. (Проблемы машиностроения, 2011)
The paper deals with an optimization problem of packing identical circles into a multiply connected region whose frontier consists of arcs of circles and line segments. On the ground of the characteristics of a mathematical model a solution method is offered. The method consists of a combination of a method of generating starting points, a modification of the feasible directions method to search for local maxima and a modification of the decremental neighbourhood search method to find an approximation to a global maximum. Numerical examples are given.